The Development of Lesson Plan are Using Problem Based Learning Model on Students Learning Outcome on Newton's Law Material : Pengembangan Rencana Pelaksanaan Pembelajaran Menggunakan Model Problem Based Learning terhadap Hasil Belajar Siswa pada Materi Hukum Newton - Halubangga, Fricilia Anggriyani; Yusuf, Frida Maryati; Buhungo, Trisnawaty Junus; Abdjul, Tirtawaty; Paramata, Dewi Diana; Yusuf, Muhammad (SEJ (Science Education Journal), 2024)
This research aims to produce a feasible (valid, practical and effective) learning implementation plan using the Problem Based Learning learning model on student learning outcomes on Newton's Law material carried out at SMP Negeri 1 Suwawa Timur. This research is development research by Thiagarajan, Semmel and Semmel, namely a 4D development model which includes four stages (define, design, develop and disseminate). Data collection techniques are carried out through observation, questionnaires, tests. Data analysis uses descriptive analysis. The research results show that: 1) The validity of the RPP developed was determined through expert validation of 92.50% with very good criteria; 2) Practicality is determined through learning implementation of 94.17% with very good criteria, student activity of 93.17% with very good criteria, and student responses with an average of all aspects of 93.85% with very good criteria; 3) Effectiveness is determined through student learning outcomes with an N-Gain value of 0.77% high criteria. Based on the research results, it can be concluded that the development of a Learning Implementation Plan using the Problem Based Learning model for student learning outcomes on Newton's Law material is suitable for use and meets the criteria of being valid, practical and effective.